Perbandingan Rekrutmen Hakim Mahkamah Konstitusi Indonesia dengan Jerman - Ulum, Miftakhul; Diniyanto, Ayon (Sharia Faculty, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The Constitutional Court in a country has a very important role for the implementation of the constitution in a country, so the recruitment process is ensured to be carried out transparently, participatively, objectively and accountably. The principles of the constitutional judge recruitment mechanism have not been implemented properly, because the law does not clearly regulate the parameters of the selection mechanism. Talking about the recruitment process for Constitutional Court judges. Germany which is considered an independent country in carrying out the recruitment process for constitutional judges. This study aims to explain the comparison and legal consequences of the recruitment process for Constitutional Court judges in Indonesia and Germany. In Indonesia, the nomination process for Constitutional Court judges is carried out by President, the House of Representatives (DPR), and the Supreme Court (MA). While in Germany it is proposed by the Bundestag and Bundesrat. Each proposing institution creates a mechanism for selecting Constitutional Court judges and integrates it with a reliable and professional merit system. Germany in an effort to accelerate and increase the efficiency of the recruitment process for Constitutional Court judges can consider several things, including determining the consensus deadline.